Treatment of Hoof Diseases in Large Ruminants - Sagizbaev, M.O.; Kurbaniyazova, G.M.; Yusupov, A.R.; Dauletbaev, N.P. (American Journal of Bioscience and Clinical Integrity, 2026)
Rustergol ulcer is a significant hoof disorder affecting cattle, causing lameness, reduced productivity, and welfare concerns. This study investigated the prevalence of Rustergolz ulcers and compared the efficacy of two treatment protocols: conventional 10% tetracycline ointment and a combination of Amoxicillin 150 antibiotic with Butofan biostimulator. Clinical observations, wound management, and healing outcomes were recorded over a 27-day period. The results demonstrated faster recovery and improved general condition in cattle treated with Amoxicillin and Butofan, highlighting their effectiveness in managing Rustergol ulcers.